Constellations of elliptical inclined lunar orbits providing polar and global coverage - Ely, Todd A.; Lieb, Erica (Pasadena, CA : Jet Propulsion Laboratory, National Aeronautics and Space Administration, 2005., 2005)
Prior results have developed a methodology for selecting a long-lived constellation of 3 satellites that provide persistent, stable coverage to either the North or South Pole with no requirement for stationkeeping under the influence of only gravitational perturbations. In the present study, the sensitivity of this coverage in the presence of non-gravitational forces is determined, and a design strategy is formulated that minimizes any potential sensitivity to these accelerations. NASA